Product Islamization as a Marketing Strategy in the Resik V â€œSekarang Berhijabâ€ Advertisement in 2012 - Koirudin, Kolik; Habsari, Sri Kusuma; Ardianto, Deny Tri (Bina Nusantara University, 2020)
This research aimed to know why did Resik V transform its product advertisement by Islamization? How did the advertisement put and negotiate the Islamic symbols and codes on womenâ€™s feminine area cleansing products? The researchers would carry out textual data analysis for the 2012 version of Resik V â€œSekarang Berhijabâ€ advertisement using Roland Barthesâ€™s semiotics theory. The results show that the advertisement utilizes the symbols of the hijab and the Indonesian Ulema Councilâ€™s label as commodities to put the Resik V product closer to Islam, as Islamic values attracted great attention from the society at that time that leaded to consumption activity. However, the Islamization in the Resik V product has ruled out the context of the hijab and halal concepts themselves, namely faith.Â